Patriotic upbringing as a defining factor of Personality formation - Katshibekova Zh5Ybyraimzhanov К1, Zhabykbayeva D2, Asanbekova G3, Shakirova A4, (Opción, 2019)
The article deals with the problems of the transformation of the spiritual and cultural values of society from the point of view of new approaches to the current stage of the socio-political development of Kazakhstan via comparative qualitative research methods. As a result, a citizen with a capital letter, seek to obtain new knowledge, mastering new technologies, easily processing the flow of new information. In conclusion, an appeal to scientific research in the provision of the patriotic upbringing of students is a socio-pedagogical problem.